ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS DAN GROWTH TERHADAP KEBIJAKAN DIVIDEN - Lestari, Mei (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is to test the influence of profitability variable by using Return on Assets (ROA) calculation, Liquidity by using Current Ratio (CR) calculation and Growth (growth of sales), to the Dividend Payout Ratio (DPR) on companies which are listed in Indonesia Stock Exchange (IDX) in 2009-2012 periods. Purposive sampling is used as sampling technique and 11 companies have been selected as samples. The analysis techniques are multiple regressions with the smallest quadratic equation and hypothesis test which is performed by using t statistics to test partial regression coefficient and f statistics to test the significance influence simultaneously with level of significance 5%. Moreover, classic assumption test which includes normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test is also performed in this research. The result of analysis of analysis shows that profitability variable has positive influence to the Dividend Payout Ratio. Liquidity has not influence to the Dividend Payout Ratio and Growth has not influence to the Dividend Payout Ratio. The prediction capability of these three variables to the DPR is 19.4% as it has been shown by adjusted R square 19.4% while the remaining is influences by other factors that are not included in the research model.Keywords: profitability, liquidity, growth, dividend policy